Improving the relevance of paleontology to climate change policy - Kießling, Wolfgang; Smith, Jansen; Raja, Nussaïbah Begum (Proceedings of the National Academy of Sciences of the United States of America, 2023)
Paleontology has provided invaluable basic knowledge on the history of life on Earth. The discipline can also provide substantial knowledge to societal challenges such as climate change. The long-term perspective of climate change impacts on natural systems is both a unique selling point and a major obstacle to becoming more pertinent for policy-relevant bodies like the Intergovernmental Panel on Climate Change (IPCC). Repeated experiments on the impacts of climate change without anthropogenic disturbance facilitate the extraction of climate triggers in biodiversity changes. At the same time, the long timescales over which paleontological changes are usually assessed are beyond the scope of policymakers. Based on first-hand experience with the IPCC and a quantitative analysis of its cited literature, we argue that the differences in temporal scope are less of an issue than inappropriate framing and reporting of most paleontological publications. Accepting that some obstacles will remain, paleontology can quickly improve its relevance by targeting climate change impacts more directly and focusing on effect sizes and relevance for projections, particularly on higher-end climate change scenarios.
CRIS-Team Scopus Importer:2023-02-17
Keywords: biodiversity; climate change; IPCC; paleobiology